How to prepare for the TOEFL test of English as a foreign language - Shape, Palmela J., Ph. D.; Trương Hùng; Nguyễn Quang Huy (Hà Nội : Thanh niên, 2000)
Sách giúp bạn đọc luyện thi thành công Toefl trong việc học Anh ngữ của mình.
Keywords: Anh ngữ; English language; Toefl; English language -- Study and teaching